Al-Qarafi’s Perspective on the Determination of Agricultural Zakat Amounts - Izbik Muhammad (Sharia and Law Faculty of Sunan Kalijaga Islamic State University Yogyakarta, 2025)
Abstract: The provisions governing agricultural zakat rates derived from hadith are often understood as fixed numerical stipulations that are not subject to change. Such an understanding gives rise to various problems when confronted with the socio-economic dynamics of modern society, particularly in relation to production costs, agricultural systems, and patterns of distribution. This article aims to analyze how al-Qarāfī positions the hadith on zakat rates as a source of law and how the position of Rasūlullāh is to be understood when conveying these provisions. The study employs a normative legal approach using qualitative library-based research, with hadiths concerning agricultural zakat rates as the primary sources, examined alongside historical evidence of pre-Islamic and post legislation systems of levies. The analysis applies al-Qarāfī’s theoretical framework concerning the differentiation of the Prophet’s status as a conveyor of risālah and as a al-ḥākim exercising ijtihād within the domain of legal policy. The findings indicate that the ‘usyr provision in agricultural zakat cannot be separated from its historical context and the socio-economic structure of Arab society at the time, nor from the capacity of Rasūlullāh as a political leader who reorganized systems of fiscal obligation. From al-Qarāfī’s perspective, the zakat rate provisions are more appropriately understood as contextual legal policies oriented toward justice rather than as rigid prescriptions of maḥḍah worship that are insulated from change. This perspective allows for a legal interpretation that preserves the authority of hadith while simultaneously accommodating flexibility in response to evolving socio-economic conditions. Abstrak: Ketentuan miqdar zakat pertanian yang bersumber dari hadis sering dipahami sebagai ketetapan angka yang bersifat baku dan tidak dapat berubah. Pemahaman tersebut memunculkan berbagai problematika ketika dihadapkan dengan dinamika sosial ekonomi masyarakat modern, terutama terkait biaya produksi, sistem pertanian, dan praktik distribusi hasil. Artikel ini bertujuan menganalisis bagaimana al-Qarāfī menempatkan hadis ketentuan tarif zakat sebagai sumber hukum serta bagaimana posisi Rasūlullāh ketika menyampaikan ketentuan tersebut. Penelitian ini merupakan penelitian hukum normatif dengan pendekatan kualitatif berbasis studi pustaka, menggunakan hadis-hadis tentang tarif zakat pertanian sebagai data utama yang dikaji bersama fakta sejarah pungutan pra-Islam dan pasca pensyariatan zakat. Analisis dilakukan dengan menggunakan teori al-Qarāfī tentang pembedaan status Nabi sebagai penyampai risālah dan sebagai al-ḥākim yang berijtihad dalam wilayah kebijakan hukum. Hasil kajian menunjukkan bahwa ketentuan ‘usyr dalam zakat pertanian tidak dapat dilepaskan dari konteks sejarah dan struktur sosial ekonomi Arab saat itu, serta dari kapasitas Rasulullah sebagai pemimpin politik yang melakukan penataan sistem pungutan. Dalam perspektif al-Qarāfī, ketentuan tarif tersebut lebih tepat dipahami sebagai kebijakan hukum yang kontekstual dan berorientasi pada keadilan, bukan sebagai ketetapan ibadah maḥḍah yang tertutup dari dinamika. Pemahaman ini membuka ruang penafsiran hukum yang tetap menjaga otoritas hadis, sekaligus memungkinkan fleksibilitas dalam merespons perubahan kondisi sosial ekonomi.